Tunable Single‐Molecule White‐Light Emission in Stimuli‐Responsive Hydrogel. Issue 6 (13th January 2020) - Wang, Jie; Tang, Fu; Wang, Yue; Liu, Shuqi; Li, Lidong
Abstract: White‐light emitting materials based on single‐molecules are of great interest owing to the simple fabrication process and good stability of such materials. However, among limited reports on single‐molecule white light‐emitting materials, the majority of systems are based on organic solvents. Here, a single‐molecule white‐light emitting hydrogel is prepared through the combination of a protonation sensitive fluorophore with a temperature sensitive hydrogel. The mechanism of this system is based on adjusting the ratio of protonated and deprotonated fluorophores through the thermally controllable hydrophobic property of the hydrogel internal microstructure. The fluorophore emits intense blue and yellow emission in its protonated and deprotonated states, respectively; hence, the luminescence of the hydrogel changes color as a function of temperature and [H + ], achieving a white color under certain conditions. On the basis of these results, a multicolor light‐emitting device (LED) and a white‐light LED are realized by placing the prepared hydrogel on a conductive substrate over a UV LED chip. Abstract : Stimuli‐responsive white‐light emitting hydrogels are fabricated based on a single‐molecule luminescent system. The temperature sensitive hydrophobic properties of the hydrogel microstructure control the protonation of the fluorophore. As an emitting layer, the single‐molecule containing hydrogel‐enabled multicolor and white‐light, light emission in a light‐emitting diode configuration with control is realized by adjusting the substrate temperature through the applied voltage.